Hepatitis E Epidemic, Uganda - Teshale, Eyasu H. (Centers for Disease Control and Prevention, 2010)
In October 2007, an epidemic of hepatitis E was suspected in Kitgum District of northern Uganda where no previous epidemics had been documented. This outbreak has progressed to become one of the largest hepatitis E outbreaks in the world. By June 2009, the epidemic had caused illness in >10,196 persons and 160 deaths.